2022
DOI: 10.5194/acp-22-14441-2022
|View full text |Cite
|
Sign up to set email alerts
|

Predicting atmospheric background number concentration of ice-nucleating particles in the Arctic

Abstract: Abstract. Mixed-phase clouds (MPCs) can have a net warming or cooling radiative effect on Earth's climate influenced by the phase and concentration of cloud particles. They have received considerable attention due to high spatial coverage and occurrence frequency in the Arctic. To initiate ice formation in MPCs at temperatures above −38 ∘C, ice-nucleating particles (INPs) are required, which therefore have important implications on the radiative properties of MPCs by altering the ice-to-liquid ratio of hydrome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 56 publications
(59 reference statements)
2
25
0
Order By: Relevance
“…The parameterization from Li et al ( 2022) compares very well with the parameterization suggested for the mix type in our study, with both sharing a very similar slope and the concentration of the latter being only a factor of ≈ 3 lower. This is not surprising, as the parameterization by Li et al (2022) was derived from measurements taking place in October and November 2019 and in March and April 2020, but further south on Svalbard. These months largely overlap with those that were found to be dominated by the mix type in our study (November) or not having a clearly dominating type (April and May), which clearly highlights the need to carry out long-term measurements as done in the present paper in order to get the right understanding of the dynamics and processes of environmental parameters such as INPs.…”
Section: Arctic Inp Parameterizationmentioning
confidence: 87%
See 3 more Smart Citations
“…The parameterization from Li et al ( 2022) compares very well with the parameterization suggested for the mix type in our study, with both sharing a very similar slope and the concentration of the latter being only a factor of ≈ 3 lower. This is not surprising, as the parameterization by Li et al (2022) was derived from measurements taking place in October and November 2019 and in March and April 2020, but further south on Svalbard. These months largely overlap with those that were found to be dominated by the mix type in our study (November) or not having a clearly dominating type (April and May), which clearly highlights the need to carry out long-term measurements as done in the present paper in order to get the right understanding of the dynamics and processes of environmental parameters such as INPs.…”
Section: Arctic Inp Parameterizationmentioning
confidence: 87%
“…This analysis was done based on Ott (1990), who suggested that log-normal distributions occur for atmospheric parameters, arising from successive random dilutions by different atmospheric processes during transportation from sources to measurement sites (as, e.g., VRS). This has been adopted for INP concentrations at different temperatures by studies such as Schrod et al (2020), Welti et al (2018) and recently Li et al (2022). Figure 4 shows the frequency distributions as well as their respective log-normal fits for the same three temperatures that were selected for the N INP time series (−12, −16 and −20 • C).…”
Section: Spectra Characterization and Frequency Distribution Of N Inpmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant progress has been made during the last years regarding the characterization of local Arctic ice-nucleating particles (INPs) (Creamean et al, 2018(Creamean et al, , 2019(Creamean et al, , 2022Zeppenfeld et al, 2019;Wex et al, 2019;Hartmann et al, 2021;Li et al, 2022;Sze et al, 2022). In a remote environment such as the Arctic where particle concentrations are generally low, local production of biogenic INPs contributes significantly to the INP population in summer (Creamean et al, 2018;Wex et al, 2019) and influence ice nucleation in the lower troposphere.…”
mentioning
confidence: 99%